A criação de agência reguladora para o setor de seguros privados, resseguro, previdência complementar aberta e capitalização na percepção de executivos do setor - Carneiro, Alessandra Vasconcelos Araújo Rodrigues (2016)
This study's purpose is the study of the governance model of the Superintendency of Private Insurance - SUSEP, common autarchy, confronting it with the special autarchy, mainly with the regulatory agencies. The study originated in exploratory research through interviews with executives who work and have extensive experience in the private insurance industry, reinsurance, open private pension and capitalization. As the observations made in interviews, the main characteristic problems of the current governance model Susep are no organizational independence and financial and budgetary autonomy. This work has deepened in the national literature understanding these characteristics within the brazilian federal regulatory agencies, in contrast to the current peculiar characteristics of the governance model of common autarchy. The model of regulatory agencies was chosen because most of the interviewees expressed understanding in the sense that the current governance model of Susep is outdated and that the adoption of the regulatory agency model would be the most appropriate for the sector. Specialized law and doctrine regulatory agencies were consulted, so as Tax and Economic Laws. There were examinated judgments of the Court of Audit and researches, national reports and studies carried out in the fields of organic independence and financial autonomy and budget of brazilian federal regulatory agencies. There were also analyzed several bills pending in Congress that propose changes in the organizational structure of the brazilian federal regulatory agencies and laws dealing with financial management and budget of these agencies. Finally, it was concluded that although the creation of a regulatory agency for the private insurance industry, reinsurance, open private pension and capitalization can contribute to overcoming problems associated with the current model of governance of Susep, such a model will not bring a definitive solution to the current problems in the Susep regarding the lack of organizational independence and financial and budgetary autonomy of the organ. Furthermore, although the regulatory agency model may present advantages over common autarchy model, the governance model of the brazilian federal regulatory agencies needs to be improved to ensure greater independence and effective financial and budgetary autonomy.